Analysis of the Needs for Moocs Assisted Digital Modules in Solar System Materials to Improve Learning Motivation in Class VII Students of SMPN 01 Bengkulu City - Okta Rahma Putri (CV Media Inti Teknologi, 2023)
This study aims to determine students' needs for the development of MOOCs-assisted digital modules in class VII solar system material at SMPN 01 Bengkulu City. This research is motivated by the lack of motivation of students to learn in science lessons. This research method uses the RnD method using a type of quantitative approach with research data collection techniques using a questionnaire in the form of Google from which data analysis techniques can be accessed online which was carried out on January 23-24 2023. The results of the needs analysis that has been carried out, obtained 54, 2% of students who find it difficult to understand science lessons, 67.5% of students are interested in using web-based electronic media, the average percentage obtained is 75, 9% which means that digital modules are needed by students. The conclusion in this study is that the development of MOOCs-assisted digital modules is quite needed in its developers to support student learning.